2012
DOI: 10.1136/archdischild-2012-302724.0432
|View full text |Cite
|
Sign up to set email alerts
|

432 Nutritional Knowledge, Attitude and Practice of High School Girls Living in Kuwait: a Pilot Study

Abstract: The purpose of this work is to do a research on the level of awareness about sexually transmitted diseases (STD) of adolescence and the factors effecting it. Method A number of adolescent at the ages of 14-17 (n=527) were asked to complete a survey questioning their level of knowledge of STDs and their sociological and demographical issues.Data were entered into the SPSS 15.0 program and evaluated. A value of p<0.05 was assumed for statistical significance. Findings 78.9% of the adolescent responded positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Dietary assessment construct terms included dietary intake ( n = 36, Additional file 7 ), dietary habits ( n = 1) [ 65 ], behaviours ( n = 1) [ 54 ], nutrition practice ( n = 1) [ 66 ] and nutrition patterns ( n = 1) [ 67 ], with additional dietary pattern analysis or dietary quality scores being calculated ( n = 3) [ 68 70 ]. Papers measuring dietary intake varied in methodology, using food frequency questionnaires (FFQ) ( n = 18) [ 69 86 ], fruit and vegetable screeners ( n = 6) [ 87 92 ], fat screeners ( n = 2) [ 37 , 43 ], dietitian conducted 24-h recalls ( n = 3) [ 93 95 ], automatic 24-h recalls ( n = 3) [ 68 , 96 , 97 ], a one week food diary ( n = 1) [ 98 ], short food frequency measure ( n = 1) [ 99 ] or brief questions to measure food frequency across select food groups ( n = 2) [ 60 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dietary assessment construct terms included dietary intake ( n = 36, Additional file 7 ), dietary habits ( n = 1) [ 65 ], behaviours ( n = 1) [ 54 ], nutrition practice ( n = 1) [ 66 ] and nutrition patterns ( n = 1) [ 67 ], with additional dietary pattern analysis or dietary quality scores being calculated ( n = 3) [ 68 70 ]. Papers measuring dietary intake varied in methodology, using food frequency questionnaires (FFQ) ( n = 18) [ 69 86 ], fruit and vegetable screeners ( n = 6) [ 87 92 ], fat screeners ( n = 2) [ 37 , 43 ], dietitian conducted 24-h recalls ( n = 3) [ 93 95 ], automatic 24-h recalls ( n = 3) [ 68 , 96 , 97 ], a one week food diary ( n = 1) [ 98 ], short food frequency measure ( n = 1) [ 99 ] or brief questions to measure food frequency across select food groups ( n = 2) [ 60 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nutrition knowledge was measured across 33 papers (Additional file 7 ), with 15 using the construct term ‘ Nutrition knowledge ’ with various FN-focused questions observed, including local dietary guideline recommendations ( n = 8) [ 63 , 71 , 101 – 106 ], nutrient content and/or functions ( n = 7) [ 56 , 63 , 71 , 77 , 104 , 105 , 107 ], diet-disease relationship ( n = 4) [ 63 , 104 , 106 , 108 ], food safety and/or hygiene ( n = 5) [ 71 , 77 , 106 – 108 ]. Seventeen additional papers included nutrition knowledge under different construct terms or scores including nutrition literacy [ 109 ], knowledge of nutrition score and a knowledge of nutrients functions score [ 66 ], healthy food choices knowledge score [ 110 ], or combined in a multi-faceted construct that included nutrition knowledge along with attitudes and practices questions [ 111 ]. Where constructs were identified separately as knowledge or attitudes they have been allocated to each specific thematic category.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Little is known about the current levels of nutritional knowledge in young people living in Kuwait. Recent studies reported low overall nutritional knowledge in high-school and college students in Kuwait (6,7). Successful school interventions have been reported in other regions, with some showing improvements in children's diets with an increase in nutritional knowledge (8,9).…”
Section: Introductionmentioning
confidence: 99%